Characterization of organic-inorganic hybrid coatings for corrosion protection of galvanized steel and electroplated ZnFe steel - de Souza, Maria Eliziane Pires (2006)
The development of hybrids materials has been extensively investigated in recent years. The combination of a wide variety of compositions and production processes had permitted the use of these materials in different applications like coatings for corrosion protection of metals. In this worko organic-inorganic hybrid materials have been prepared from the hydrolysis of tetraethylorthosilicate and silanol-terminated polidymetilmetoxysilane using a sol-gel process. These materials have been applied on galvanized steel and on steel electroplated with a ZnFe. In order to evaluate the degradation behavior of these coatings, electrochemical techniques (Electrochemical Impedance Spectroscopy and Potentiodynamic Polarization) were used. EIS data was fitted to an equivalent circuit from which the electrochemical parameters were obtained. Results show a good protective character of the hybrid films, when compared with uncovered specimens. The overall performance of the coating systems appears to be highly dependent on the kind of metallic coating applied to the steel.